Generalized Invexity and Duality in Multiple Objective Variational Problems - Mukherjee, R.N.; Mishra, S.K. (My University, 1995)
Multiple objective programming problems with the concept of weak minima are extended to multiple objective variational problems. A number of weak, strong, and converse duality theorems are given under a variety of generalized invexity conditions.
Keywords: Multiple objective programming; minima; converse duality theorem; invexity